Visualization and spatial mapping of PFAS in the edible storage root of radish - Yuwei Zuo; Weilan Zhang (Journal of Hazardous Materials Letters)
Plants, as key components of trophic networks, play a critical role in the bioaccumulation of PFAS and their transfer to higher trophic levels. This study introduces an innovative methodology using timsTOF fleX MALDI-2 to visualize the spatial distribution of PFAS in plant tissues. Radish was selected as the model plant due to its global popularity as a widely consumed vegetable. DAN (1,5-diaminonaphthalene) was used as the MALDI matrix, and the mass spectrometry operating conditions were optimized to acquire the best PFAS signals. The results show that long-chain PFAS predominantly accumulated in the xylem of the edible storage root, where their high hydrophobicity limits upward translocation. In contrast, short-chain PFAS and PFOA exhibited stronger signals in the cortex and periderm, likely due to alternative transport pathways. This differential distribution highlights the significant influence of PFAS physicochemical properties, such as chain length and hydrophobicity, on their in-planta transport mechanisms. By precisely mapping PFAS within plant tissues, this study provides a powerful tool for identifying high-risk edible tissues and assessing human exposure risks through PFAS-contaminated crops. It also reinforces the urgent need for sustainable remediation strategies to reduce PFAS levels in agricultural systems, thereby safeguarding food safety, ecosystem health, and human well-being.